Optimism Shapes Mindset: Understanding the Association of Optimism and Pessimism - Dardick, William R.; Tuckwillber, Elizabeth D. (Journal of Interdisciplinary Studies in Education, 2019)
The present study investigated our hypothesis of an underlying relationshipbetween optimism/pessimism and implicit theories of intelligence. Weinvestigated the psychometric properties of optimism and mindset scales inour sample, compared confirmatory factor analysis models of the scales,examined the full measurement model to confirm quality measurement of thefinal structural phase of investigation, and finally conducted two competingstructural equation models. We found that the direct pathway from optimismto growth mindset was significant, and the pathway from pessimism to fixedmindset was also significant. However, there were no significant direct effectsof optimism on fixed mindset or pessimism on growth mindset. Measurement,research, and practice implications are discussed.